Annual Characteristics of Runoff and Sediment in West River and North River Delta and Their Influencing Factors - ZHANG Yonghua; LU Yongqiu (Renmin Zhujiang)
The analysis of annual characteristics of runoff and sediment based on the monthly measured hydrological data of Makou Station and Sanshui Station in the West River and North River delta over the past 50 years.It shows that the monthly runoff,sediment discharge,and sediment concentration of Makou Station and Sanshui Station are obviously of the “unimodal type”,with runoff and sediment concentrated in June and July during the flood season.The annual concentration ratio of runoff and sediment in the West River and North River delta is high with a decreasing trend,while the concentration period is concentrated in early July with a slight delay.The interannual variation trend of runoff and sediment in the West River and North River delta is mainly controlled by the variation of flood season and is affected to some extent by the regulation of the non-flood period.There is a consistent interannual trend of runoff with precipitation,but the annual concentration ratio is more affected by hydraulic engineering.Sand excavation in river channels affects the distribution of runoff and sediment by changing the diversion ratio of runoff and sediment.